WFDC21P promotes triple-negative breast cancer proliferation and migration through WFDC21P/miR-628/SMAD3 axis - Wei, Yu-Bo; Liang, Dong-Min; Zhang, Mei-Ling; Li, You-Jie; Sun, Hong-Fang; Wang, Qin; Liang, Yan; Li, Yan-Mei; Wang, Ran-Ran; Yang, Zhen-Lin; Wang, Pingyu; Xie, Shu-Yang (Frontiers in Oncology, 2022)
Long non-coding RNAs (lncRNAs) modulate cell proliferation, cycle, and apoptosis. However, the role of lncRNA-WFDC21P in the tumorigenesis of triple-negative breast cancer (TNBC) remains unclear. Results of this study demonstrated that WFDC21P levels significantly increased in TNBC, which was associated with the poor survival of patients. WFDC21P overexpression significantly promoted TNBC cell proliferation and metastasis. WFDC21P interacted with miR-628-5p, which further suppressed cell proliferation and metastasis by negatively regulating Smad3-related gene expression. Recovery of miR-628-5p weakened the roles of WFDC21P in promoting the growth and metastasis of TNBC cells. Moreover,N6-methyladenosine (m6A) modification upregulated WFDC21P expression in the TNBC cells. WFDC21P and its m6A levels were increased after methyltransferase like 3 (METTL3) overexpression but reduced after METTL3 silencing. The proliferation and metastasis of TNBC cells were promoted by METTL3 overexpression but suppressed by METTL3 silencing. This study demonstrated the vital roles of WFDC21P and its m6A in regulating the proliferation and metastasis of TNBC cells via the WFDC21P/miR-628/SMAD3 axis.